Pengaruh Jumlah dan Panjang Blade Terhadap Performa Kincir Angin - Pongbarib, Esau Irsan; Mangalla, Lukas Kano; Hasanudin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2022)
Energy needs continue to increase in line with the increasing population, while fossil energy is very limited and has a negative impact on the environment. Therefore, alternative energy sources such as wind energy are very important to be developed. This study observes the effect of the number of turbine blades and blade length on the rotation and current output. The study was conducted experimentally using the 2, 3, and 4 number of blades, while the length was varied from 10 cm, 15 cm and 20 cm. The blades performance is compared by measuring the blade rotation and current generated from an electric dynamo connected to the blade rotation. We also carried out several variations of wind speed for each number and length of the blade. The results showed that the number of blades 3 and 4 produced almost the same electric current and rotation while the number of blades of 2 was much smaller. It can also be seen that the blade length of 15 cm gives a large rotation followed by a length of 20 cm and 10 cm.Keyword: Windmill, blade length, performance